Are health facilities well equipped to provide basic quality childbirth services under the free maternal health policy? Findings from rural Northern Ghana - Philip Ayizem Dalinjong; Alex Y. Wang; Caroline S. E. Homer (BMC Health Services Research, 2018)
Abstract Background Basic inputs and infrastructure including drugs, supplies, equipment, water and electricity are required for the provision of quality care. In the era of the free maternal health policy in Ghana, it is unclear if such basic inputs are readily accessible in health facilities. The study aimed to assess the availability of basic inputs including drugs, supplies, equipment and emergency transport in health facilities. Women and health providers’ views on privacy and satisfaction with quality of care were also assessed. Methods The study used a convergent parallel mixed methods in one rural municipality in Ghana, Kassena-Nankana. A survey among facilities (n = 14) was done. Another survey was carried out among women who gave birth in health facilities only (n = 353). A qualitative component involved focus group discussions (FGDs) with women (n = 10) and in-depth interviews (IDIs) with midwives and nurses (n = 25). Data were analysed using descriptive statistics for the quantitative study, while the qualitative data were recorded, transcribed, read and coded using themes. Results The survey showed that only two (14%) out of fourteen facilities had clean water, and five (36%) had electricity. Emergency transport for referrals was available in only one (7%) facility. Basic drugs, supplies, equipment and infrastructure especially physical space were inadequate. Rooms used for childbirth in some facilities were small and used for multiple purposes. Eighty-nine percent (n = 314) of women reported lack of privacy during childbirth and this was confirmed in the IDIs. Despite this, 77% of women (n = 272) were very satisfied or satisfied with quality of care for childbirth which was supported in the FGDs. Reasons for women’s satisfaction included the availability of midwives to provide childbirth services and to have follow-up homes visits. Some midwives were seen to be patient and empathetic. Providers were not satisfied due to health system challenges. Conclusion Government should dedicate more resources to the provision of essential inputs for CHPS compounds providing maternal health services. Health management committees should also endeavour to play an active role in the management of health facilities to ensure efficiency and accountability. These would improve quality service provision and usage, helping to achieve universal health coverage.